2022
DOI: 10.3389/fpls.2021.832044
|View full text |Cite
|
Sign up to set email alerts
|

Herbaceous Dominant the Changes of Normalized Difference Vegetation Index in the Transition Zone Between Desert and Typical Steppe in Inner Mongolia, China

Abstract: Asymmetric responses of aboveground net primary productivity (ANPP) to precipitation were identified as a signal to predict ecosystem state shifts at temperate grassland zones in Inner Mongolia, China. However, mechanism studies were still lacking. This study hypothesized that the enhanced growth and newly emerged herbaceous after increased precipitation resulted in the highest asymmetry at the transition zone between desert and typical steppe. We monitored the responses of the normalized difference vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The normalized difference vegetation index (NDVI) constructed by the red and near-infrared spectral bands is considered to be closely related to vegetation coverage and productivity ( Huete et al., 2002 ), which makes it one of the most widely utilized remotely sensed indices to investigate vegetation dynamics across global and regional levels ( Myneni et al., 1997 ; Pinzon and Tucker, 2014 ; Zhou et al., 2020 ; Lv et al., 2022 ). Numerous studies have employed time series of NDVI data to examine the vegetation variations in the South China Karst region since the launch of the ecological engineering around 2000 ( Cai et al., 2014 ; Wang et al., 2015 ; Tong et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The normalized difference vegetation index (NDVI) constructed by the red and near-infrared spectral bands is considered to be closely related to vegetation coverage and productivity ( Huete et al., 2002 ), which makes it one of the most widely utilized remotely sensed indices to investigate vegetation dynamics across global and regional levels ( Myneni et al., 1997 ; Pinzon and Tucker, 2014 ; Zhou et al., 2020 ; Lv et al., 2022 ). Numerous studies have employed time series of NDVI data to examine the vegetation variations in the South China Karst region since the launch of the ecological engineering around 2000 ( Cai et al., 2014 ; Wang et al., 2015 ; Tong et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of Yinshanbeilu has arid and subarid areas; however, due to global warming, relevant studies have shown that the climate warming trend in this region has already been more pronounced during the last two decades. Moreover, annual precipitation is increasing, which has alleviated the degree of drought in Yinshanbeilu to a certain extent [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, soil–plant interactions and species coexistence in both desert and typical steppes are mainly affected by water availability (Chen et al, 2022). Precipitation in July and August plays a critical role in driving net primary productivity of grasslands in the typical to desert steppe transition zone (Lv et al, 2022). During the extended drought period, the growth of shallow‐rooted plants can be severely suppressed, and the degree of the influence can vary with soil properties (Tian et al, 2022).…”
Section: Introductionmentioning
confidence: 99%